2012
DOI: 10.1007/s10495-012-0767-5
|View full text |Cite
|
Sign up to set email alerts
|

Celastrol inhibits growth and induces apoptotic cell death in melanoma cells via the activation ROS-dependent mitochondrial pathway and the suppression of PI3K/AKT signaling

Abstract: Celastrol has been reported to possess anticancer effects in various cancers; however, the precise mechanism underlying ROS-mediated mitochondria-dependent apoptotic cell death triggered by celastrol treatment in melanoma cells remains unknown. We showed that celastrol effectively induced apoptotic cell death and inhibited tumor growth using tissue culture and in vivo models of B16 melanoma. In addition to apoptotic cell death in B16 cells, several apoptotic events such as PARP cleavage and activation of caspa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
66
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(75 citation statements)
references
References 55 publications
7
66
0
1
Order By: Relevance
“…In particular, they suggest that celastrol may inhibit the classical NF-κB pathway by preventing IκBα degradation, blocking p65 translocation and suppressing MMP-9 expression downstream of NF-κB. These results are consistent with those of previous studies (18,19,27), although other studies have suggested different mechanisms for the effects of celastrol on invasiveness (22,(35)(36)(37)(38). It should be noted that alternative mechanisms to the NF-κB pathway are also likely to contribute to the effects of celastrol on migration and invasion in the current models.…”
Section: Discussionsupporting
confidence: 90%
“…In particular, they suggest that celastrol may inhibit the classical NF-κB pathway by preventing IκBα degradation, blocking p65 translocation and suppressing MMP-9 expression downstream of NF-κB. These results are consistent with those of previous studies (18,19,27), although other studies have suggested different mechanisms for the effects of celastrol on invasiveness (22,(35)(36)(37)(38). It should be noted that alternative mechanisms to the NF-κB pathway are also likely to contribute to the effects of celastrol on migration and invasion in the current models.…”
Section: Discussionsupporting
confidence: 90%
“…The current study indicates that celastrol treatment reduced the protein expression levels of PI3K and p-Akt in OVCAR3 cells. In a previous study, Lee et al (29) indicated that treatment with celastrol was able to suppress cell growth and increase apoptosis in melanoma cells through the suppression of PI3K/AKT signaling. Sha et al (16) demonstrated that celastrol induces apoptosis in gastric cancer cells via the inhibition of the PI3K/Akt-NF-κB signaling pathway by miRNA-21.…”
Section: Discussionmentioning
confidence: 99%
“…High endogenous ROS concentrations in malignant cells may also render these cells more vulnerable to further stresses (34,39,40). Hence, anticancer therapies that trigger a further increase in ROS formation may induce cell death in cancer cells compared with their non-malignant counterparts (34,41,42). In addition, ROS can limit malignant growth by triggering activation of p53, whereas antioxidants enhanced tumor progression in a p53-dependent manner (17).…”
Section: Gr1mentioning
confidence: 99%